Agricultural Pilot's Audiological Profile - Foltz, Lucas; Soares, Carla Debus; Reichembach, Maria Adelaide Kuhl (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The agricultural airplane pilot are daily exposed to intense noises, being susceptible to the noise-induced hearing loss (NIHL) and its auditory and extra auditory effects.Objective: To analyze the audiological profile of this population, verifying the work's influence on its hearing.Method: It was realized a retrospective, individual, observational, and cross-sectional study through the data obtained by means of a questionnaire and audiometric thresholds of 41 agricultural pilots. To the statistical analysis were utilized the chi-square, Spearman, and Wilcoxon tests with significance level of 5%.Results: It was verified that 95,1% of the pilots use PPE (personal protective equipment) during flight and 58,5% have contact with pesticides. More than half of individuals referred to feel auditory and extra auditory symptoms, being the buzz the more frequent (29,1%). It has the occurrence of 29,3% of NIHL suggestive hearing loss and 68,3% of normality, taking this presence of unilateral notch in 24,4% and bilateral notch in 31,7%. It was found correlation statistically significant in the associations between time of service and the average of the acute frequencies in the right ear (p = 0038), and in the left ear (p = 0,010). It has a statistical tendency in the association between audiometric configuration and contact with pesticides (p = 0,088).Conclusion: The hearing loss prevalence in this study was showed high. More than half of the sample has normal audiometric thresholds with notch configuration. Such data lead to the conclusion that the agricultural pilots, even with PPE use, they still suffer with the damages caused by noise, needing best proposals of hearing loss prevention.
Keywords: noise-induced hearing loss; aviation; agriculture; occupational noise; worker health